MOLECULAR DOCKING ANALYSIS AND ADMET PREDICTION Of Caesalpinia sappan COMPOUNDS AS ANTIINFLAMMATORY THROUGH CYCLOOXYGENASE-2 INHIBITION - Putri Maisarah, Marisa; Rahmawati; Andika (Jurnal Insan Farmasi Indonesia, 2024)
Selective COX-2 inhibitors have been considered safer treatments than NSAIDs for inflammation from its side effect. Sappanwood was already known for its antiinflammatory activity, but its selectivity towards COX-2 has not been tested. The purpose of this study was to determine the potential activity of compounds in Caesalpinia sappan as anti-inflammatory agents by inhibiting COX-2 and determine their ADMET’s properties through in silico study. Qulified compound from Lipinski’s rule of five evaluation would be continued to the molecular docking using Autodock Tools and ADMET prediction using SwissADME and ADMETLab. Three compounds known to have the best free bond energy (ΔG) values were Caesalpiniaphenol A, Sappankalkon, and Deoxysappanone B with ΔG values respectively (-9.36 ; -9.23 ; -9.02 kcal/mol) and their inhibition constant values of (124.44 ; 172.43 ; 244.75 nM) respectively. Amino acid residues that are known to involve to the formation of hydrogen bonds in ligands are GLN 192 and PHE518. Toxicity results showed that these three compounds were predicted to be neither hepatotoxic nor hERG inhibitors, but 3-deoxysappanone B and sappankalkon was predicted to cause AMES mutagenicity and skin sensitivity. It can be concluded that these third compound has the potential as an inhibitor of the COX-2 enzyme.